A28 INCREASED EMERGENCY DEPARTMENT VISITS AND HOSPITALIZATIONS FOR INFECTIOUS DISEASES IN ELDERLY PATIENTS WITH INFLAMMATORY BOWEL DISEASE: A POPULATION-BASED MATCHED COHORT STUDY. (15th March 2019) - Kuenzig, E; Murthy, S; Stukel, T A; Nguyen, G C; Kaplan, G G; Talarico, R; Benchimol, E I
Abstract: Background: The prevalence of IBD in elderly people ≥65y is growing rapidly in Canada. This group presents unique clinical challenges due to their comorbidity burden and increased susceptibility to infection. Aims: To compare the incidence of emergency department (ED) visits and hospitalizations for infectious diseases in people with elderly-onset IBD compared to people without IBD. Methods: Incident cases of elderly IBD (≥65y at diagnosis) diagnosed between 2002–2013 were identified from health administrative data in Ontario using a validated algorithm. Cases were age- and sex-matched to five controls. ED visits and hospitalizations for infectious diseases were identified from the National Ambulatory Care Reporting System and the CIHI Discharge Abstract Database, respectively. Negative binomial models were used to compare the incidence of any infection, any gastrointestinal infection, Clostridium difficile, influenza/pneumonia, sepsis, skin infection, or urinary tract infection. Models were adjusted for rural/urban residence, income, and ADG comorbidity index. Results are presented as incidence rate ratios (IRR) and 95% confidence intervals (CI). Results: Cases of IBD, CD, and UC were at increased risk of hospitalization for all types of infections studied (Table). Of all infections analyzed, the greatest increase in the relative incidence compared to controls was seen for C. difficile (IBD: IRR 13.38, 95% CI 9.50–18.84). Patients with IBD, CD, and UC had also increased incidence of infection-related ED visits (Table). The highest relative incidence of ED visit was similarly noted for C. difficile (IBD: IRR 8.95, 95% CI 5.69–14.09). The 5-year risk of hospitalization and ED visits for any serious infection in patients with IBD were 29% and 40%, respectively, compared to 5% and 17% in controls. Conclusions: Elderly patients with IBD are at significantly increased risk of infections requiring acute care and hospitalization. Treatment strategies to minimize infections in elderly patients should be considered. Funding Agencies: CAG, CCC, CIHR